Effects of Prior-Task Success on Young and Older Adults’ Cognitive Performance an Evaluation of the Strategy Hypothesis - Patrick Lemaire; Fleur Brun (Journal of Cognition, 2018)
In prior-task success, older adults improve cognitive performance on target tasks after successfully accomplishing a prior task. We tested the hypothesis that effects of prior-task success occur via older adults’ selecting the better strategy more often and executing strategies more efficiently on each problem under a prior-task success condition. Young and older participants accomplished computational estimation tasks (i.e., providing the best estimates to arithmetic problems) under a success or a control condition. They successfully accomplished a Stroop task or accomplished no prior task before taking the target arithmetic task. Participants had to select the better strategy on each problem in Experiment 1 and to execute a cue strategy in Experiment 2. Consistent with the strategy hypothesis, older adults, but not young adults, (a) obtained better performance, (b) used the better strategy more often, (c) inappropriately repeated the same strategy less often across successive problems, and (d) executed strategies more efficiently, under a prior-task success condition relative to a control condition. These results highlight the role of strategic variations in effects of prior-task success. They have important implications when assessing age differences in human cognition during both normal and pathological aging.